Islamic banking employee loyalty level in Banda Aceh – Indonesia: An Islamic perspective - Ridwan Nurdin (Proceedings of AICS - Social Sciences, 2017)
The purpose of this paper is to assess the loyalty level of Islamic Banking employee in Banda Aceh, Indonesia based on criteria in the Islamic perspective that has been established. The writing of this paper uses the method of library study and empirical method in the form of quantitative. An investigation was conducted involving 277 respondents of Muslim Islamic banking employees in Banda Aceh, Indonesia. Data were cited using questionnaire instruments and analyzed using descriptive and inferential statistics. There are five criteria of employee loyalty in Islam, namely Amanah (Trust), Compliance to the leadership, Ikhlas (Sincerity), Responsible and Welfare at Work. The results showed that the overall level of Muslims’ employee loyalty in Islamic Banking in Banda Aceh, Indonesia is at a high level.